Checklist of marine elasmobranchs of Colombia - Andrés Felipe Navia, Paola Mejía-Falla (Pontificia Universidad Javeriana, 2019)
A review and update to the shark and ray species recorded for the marine waters of Colombia was carried out. A total of 206 species had been recorded in the literature, of which 138 species (76 sharks and 62 rays) could be confirmed from museum records, catches, photographs, and videos. No evidence was found for 25 species, but their distribution included neighboring countries, and they were therefore classified as possible based on distribution. Thirtysix species were classified as improbable based on distribution and seven more were considered as misidentifications. The inventory of confirmed species includes 57 genera (30 shark and 27 batoid genera) and 34 families (18 shark and 16 batoid families). There was notably an addition of 26 confirmed species since 2007 as well as numerous modifications to group systematics and taxonomy, especially for batoids. The total number of confirmed elasmobranchs represented 12.1% of species known worldwide, and could even reach 14.5%, indicating that Colombia has one of the richest cartilaginous fish faunas in Latin America, behind Mexico and Brazil. This demonstrates that although Colombia cannot be considered an elasmobranch biodiversity hotspot or site of elasmobranch endemism globally, it does have good representativity of these species´ biodiversity at the regional level, especially regarding amphi-American species.